Governing through non-enforcement: Regulatory forbearance as industrial policy in advanced economies - Matías Dewey; Donato Di Carlo (Regulation & Governance, 2021)
Political economy scholarship generally assumes that governments are interested in enforcing economic regulations. Cases of non-enforcement are predominantly studied in the context of developing countries and are chiefly associated with states' deficient institutional capacity. This article casts doubts on these assumptions by showing how governments in advanced democracies manipulate the regulatory regime and generate selective non-enforcement of economic regulations to shape markets at their discretion. We argue that regulatory forbearance becomes an attractive form of industrial policy when governments are prevented from intervening discretionally in markets due to legal obstacles, which they cannot overcome; or when the productive structure of the country makes alternative forms of intervention unviable. Drawing on the study of tax non-enforcement in two most-different cases of strong and weak state capacity such as Germany and Italy, the article theorizes three techniques through which governments manipulate regulatory regimes: legal and organizational sabotage and shirking. By shedding light on the economic logic of forbearance, the article points at non-enforcement as an overlooked mode of regulatory governance and suggests the need to inquire further into governments' strategic agency behind regulatory regimes.
Keywords: 330; regulatory regimes; non-enforcement; taxation; industrial policy; economic regulation